Giant hepatic haemangioma rupture in a patient on direct oral anticoagulant therapy. Issue 1 (29th January 2021) - Nguyen, Marie; Lim, Aaron E; Jeyarajan, Eshwarshanker; Koh, Mary-Ann; Ng, Andrew; Townend, Phillip
Abstract: Rupture of a liver haemangioma is extremely rare, with less than 100 cases reported in the literature. This is the first case known to date reporting a rupture occurring with direct oral anticoagulant therapy. A 76-year-old woman presented with acute abdominal pain and syncope in the context of commencing apixaban 4 weeks prior. Abdominal computed tomography and angiography demonstrated a large heterogenous mass in the left liver lobe with contrast blush suggestive of a bleeding tumour. Urgent transcatheter arterial embolization successfully ceased haemorrhage. Due to persistent compressive symptoms, a left lateral hepatectomy was performed. CD34 immunostaining of the tissue revealed variably sized vessels, which was consistent with a ruptured giant hepatic haemangioma. Our case substantiates the limited available literature regarding ruptured haemangiomas. Combined with previous case reports, this report will significantly contribute to our understanding of the risk factors, diagnosis and surgical indications for ruptured hepatic haemangiomas.